2019
DOI: 10.32491/jii.v19i3.506
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding application of garfish (Hemirhampus sp.) in North Maluku Sea

Abstract: The purpose of this study was to identify the species of garfish in the waters of north Maluku by applying DNA bar-coding techniques. The method used in the study was the primary design of DNA extraction and isolation, and DNA amplification through polymerase chain reaction. The results showed that Gen Cyt b analysis amplified ± 350 bp amplicon and for the alignment analysis showed that the amplification sample sequence had similarity with the Cyt b gene sequence of Hemiramphus balao with value of 97%. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, the diversity and number of Hemiramphus species living in this area are still unknown. The presence of Hemiramphus in Indonesia has been reported by several studies (Kawimbang et al 2012;Suryawan et al 2016;Ahmad et al 2019;Natan et al 2019). Previously, fish identification was conducted mainly by a morphological approach based on morphometric and meristic characteristics.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the diversity and number of Hemiramphus species living in this area are still unknown. The presence of Hemiramphus in Indonesia has been reported by several studies (Kawimbang et al 2012;Suryawan et al 2016;Ahmad et al 2019;Natan et al 2019). Previously, fish identification was conducted mainly by a morphological approach based on morphometric and meristic characteristics.…”
Section: Introductionmentioning
confidence: 79%
“…Ballyhoo halfbeak is commonly caught in the coastal waters of Rio Grande do Norte Brazil (Oliveira et al 2015). This fish is also an important fish commodity in the Maluku Islands (Ahmad et al 2019;Natan et al 2019), mainly caught using small circular nets (mini purse seines) called "soma roa and giop".…”
Section: Introductionmentioning
confidence: 99%
“…Akbar and Aris (2018) genetic connectivity show the closeness between populations. The low genetic distance value indicates the closeness of the kinship relationship (Achmad et al, 2019). It can be said that the sequence has a low level of diversity.…”
Section: Phylogenetic Tree Analysis and Genetic Distancementioning
confidence: 99%
“…The purpose of this identification is to obtain the genetic quality, characteristics, or character of a species, and to support taxonomic identification, so that it can be used for breeding and conservation purposes (Ragan et al, 1994;Rohani-Ghadikolaei et al, 2011;Djakatara et al, 2018;Annisaqois et al, 2018). Genetic information can be used as a conservation database to determine policy strategies and the existence of a biota (Akbar et al, 2014;Achmad et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of four lineages in mackerel (R. kanagurta) in Banda Aceh and Trang (Andaman Sea) and Can Tho (South China Sea) [29] . Previous studies discussing phylogenetic pelagic fish have been reported such as yellowfin tuna [5,19] , tuna and mackarel in the Indonesian Archipelago [30] in julung-julung fish (Hemirampus sp) [31] . Substitution probability values were found to have similarities in all nucleotide elements (Table 1).…”
Section: Phylogeneticmentioning
confidence: 99%